Prevalence and prescription patterns of oral glucocorticoids in adults: a retrospective cross-sectional and cohort analysis in France. Issue 7 (31st July 2017) - Bénard-Laribière, Anne; Pariente, Antoine; Pambrun, Elodie; Bégaud, Bernard; Fardet, Laurence; Noize, Pernelle
Abstract : Objectives: To study trends in use of oral glucocorticoids (GCs) among adults, characteristics of oral GC initiators and prescriptions for the prevention of potential adverse effects associated with GC therapy. Design: First, a cross-sectional study repeated yearly was performed from 2007 to 2014 in a nationwide representative sample. Second, characteristics of initiators and patterns of GC therapy during the year following treatment initiation were described in a cohort of patients who began GC between 2007 and 2013. Setting: Population-based study using data from the French reimbursement healthcare system (covering approximately 90% of the population) in patients aged ≥18 years. Results: Over the study period, the prevalence of oral GC use ranged from 14.7% to 17.1% (95% CI 17.0%–17.2%) with a significant increase of 14.1% (95% CI +13.5% to +14.8%). The 2007–2013 cohort of oral GC initiators comprised 206 759 individuals. Oral GC use was mostly short-term (68% of unique reimbursement) and more than half of short-term users took concurrent antibiotics or respiratory/otological drugs. Chronic users (≥6 reimbursements/year) represented 1.8% (n=3789) of the cohort. The proportion of chronic users with comorbidities likely to be worsened by GC use (diabetes, psychotic disorders, osteoporosis) was 25%. Among patients at increased risk of osteoporosis, 62% received specific prevention/monitoring measures and only 27% had a bisphosphonate. Half of chronic oral GC users had a concurrent reimbursement of a proton pump inhibitor in the absence of non-steroidal anti-inflammatory drug use. Conclusions: Oral GC use was highly widespread and increased among adults from 2007 to 2014. The overwhelming short-term use could mainly concern a growing use of unjustified prescriptions rather than situations with a favourable benefit/risk ratio. For chronic users, our findings plead for the development of interventions designed to improve monitoring with regard to the frequent comorbidities at risk and inappropriate prescribing of preventive therapeutic measures.